Melanocortin agonists stimulate lipolysis in human adipose tissue explants but not in adipocytes. (December 2015) - Møller, Cathrine; Pedersen, Steen; Richelsen, Bjørn; Conde-Frieboes, Kilian; Raun, Kirsten; Grove, Kevin; Wulff, Birgitte
Abstract Background The central melanocortin system is broadly involved in the regulation of mammalian nutrient utilization. However, the function of melanocortin receptors (MCRs) expressed directly in peripheral metabolic tissues is still unclear. The objective of this study was to investigate the lipolytic capacity of MC1-5R in differentiated adipocytes versus intact white adipose tissue. Results Non-selective MCR agonist α-MSH, MC5R-selective agonist PG-901 and MC4R-selective agonist LY2112688 significantly stimulated lipolysis in intact white adipose tissue, whereas stimulation of MCRs in differentiated adipocytes failed to do so. The lipolytic response of MC5R was decreased in intact human white adipose tissue when co-treating with β-adrenergic antagonist propranolol, suggesting that the effect may be dependent on neuronal innervation via noradrenalin release. Conclusion When developing an anti-obesity therapeutic drug with selective MC4R/MC5R properties, effects on lipolysis in white adipose tissue may be physiologically relevant.